Ex Vivo Antioxidant Capacities of Fruit and Vegetable Juices. Potential In Vivo Extrapolation - Alexis Matute; Jessica Tabart; Jean-Paul C; Claire Kevers; Jacques Dommes; Jean-Olivier Defraigne; Joël Pincemail (MDPI AG, 2021)
Background: In support of claims that their products have antioxidant properties, the food industry and dietary supplement manufacturers rely solely on the in vitro determination of the ORAC (oxygen radical antioxidant capacity) value, despite its acknowledged lack of any in vivo relevance. It thus appears necessary to use tests exploiting biological materials (blood, white blood cells) capable of producing physiological free radicals, in order to evaluate more adequately the antioxidant capacities of foods such as fruit and vegetable juices. Materials: Two approaches to assessing the antioxidant capacities of 21 commercial fruit and vegetable juices were compared: the ORAC assay and the "PMA-whole blood assay," which uses whole blood stimulated by phorbol myristate acetate to produce the superoxide anion. We described in another paper the total polyphenol contents (TPCs) and individual phenolic compound contents of all the juices were investigated. Results: Ranking of the juices from highest to lowest antioxidant capacity differed considerably according to the test used, so there was no correlation (r = 0.33, p = 0.13) between the two assays when considering all juices. Although the results of the ORAC assay correlated positively with TPC (r = 0.50, p = 0.02), a much stronger correlation (r = 0.70, p = 0.004) emerged between TPC and % superoxide anion inhibition. In the PMA-whole blood assay, peonidin-3-O-glucoside, epigallocatechin gallate, catechin, and quercetin present in juices were found to inhibit superoxide anion production at concentrations below 1 µM, with a strong positive correlation. Conclusions: Associated with the determination of total and individual phenolic compounds contained in fruit and vegetable juices, the PMA-whole blood assay appears better than the ORAC assay for evaluating juice antioxidant capacity.